Journal of prosthodontics on complex restorations - Baba, Nadim Z.; Guichet, David L.; American College of Prosthodontists (Hoboken, New Jersey : Wiley Blackwell, 2016)
Journal of Prosthodontics on Complex Restorations compiles 34 of the journal's best articles discussing complex restorative dental challenges, collecting notable works on the subject. -Presents a curated list of the best peer-reviewed articles on complex restorations from the pages of Journal of Prosthodontics -Covers management of maxillofacial defects using CAD/CAM technology, tooth wear, congenital disorders, orthodontic/prosthodontic patients, patients with surgical and maxillofacial challenges, and completely edentulous patients using new ceramic material -Offers a mix of clinical reports, research articles, and reviews.
Compilation of articles from Journal of Prosthodontics.
Includes bibliographical references and index.
Print version of record.
Keywords: Prosthodontics; Fillings (Dentistry) -- Methods; MEDICAL -- Surgery -- General; MEDICAL -- Dentistry -- Prosthodontics; Fillings (Dentistry); Prosthodontics; Prosthodontics -- Methods; Dental Restoration, Permanent -- methods; Electronic books; Methods (Music); Collected Works